Strand 3: Teaching over the Internet: How is the UK's Open University doing it? - Wilson, Tina; Whitelock, Denise; Simpson, Nicky; Greenwood, Jillian (Proceedings of the International Conference on Networked Learning, 1998)
Will the Internet becoming the main delivery and communication medium for Life Long Learning? At the Open University in the United Kingdom the Internet provides teaching and learning opportunities for courses in the domains of Computing, Technology, Arts, Science, Social Science, Education and the Open Business School. This paper discusses the issues arising from the many pilot studies which have taken place to date and includes data from our larger scale survey with 29 course teams and suggests a future research agenda for this area.